Perceived Neighborhood Safety Is Associated with Poor Sleep Health among Gay, Bisexual, and Other Men Who Have Sex with Men in Paris, France - Duncan, Dustin T. (J Urban Health, 2017)
Recent studies have examined sleep health among men who have sex with men (MSM), but no studies have examined associations of neighborhood characteristics and sleep health among this population. The purpose of this study was to examine associations between perceived neighborhood safety and sleep health among a sample of MSM in Paris, France. We placed broadcast advertisements on a popular smartphone application for MSM in October 2016 to recruit users in the Paris (France) metropolitan area (n = 580). Users were directed to complete a web-based survey, including previously used items measuring perceptions of neighborhood safety, validated measures of sleep health, and socio-demographics. Modified Poisson models were used to estimate risk ratios (RRs) and 95% confidence intervals (CI) for the associations between perceived neighborhood safety and the following outcomes: (1) poor sleep quality, (2) short sleep duration, and (3) self-reported sleep problems. Poor sleep health was common in our sample; e.g., 30.1% reported poor sleep quality and 44.7% reported problems falling asleep. In multivariate regression models, perceived neighborhood safety was associated with poor sleep quality, short sleep duration, and having sleep problems. For example, reporting living in a neighborhood perceived as unsafe during the daytime (vs. safe) was associated with poor sleep quality (aRR, 1.60; 95% CI, 1.01, 2.52), short sleep duration (aRR, 1.92; 95% CI, 1.26, 2.94), problems falling asleep (aRR, 1.57; 95% CI, 1.17, 2.11), and problems staying awake in the daytime (aRR, 2.16; 95% CI, 1.05, 4.43). Interventions to increase neighborhood safety may improve sleep health among MSM.